Nuclear Fusion One Noble Goal and a Variety of Scientific and Technological Challenges - Girka, Igor (IntechOpen, 2019)
Power production and its consumption and distribution are among the most urgent problems of mankind. Despite positive dynamics in introducing renewable sources of energy, nuclear power plants still remain the major source of carbon-free electric energy. Fusion can be an alternative to fission in the foreseeable future. Research in the field of controlled nuclear fusion has been ongoing for almost 100 years. Magnetic confinement systems are the most promising for effective implementation, and the International Thermonuclear Experimental Reactor is under construction in France. To accomplish nuclear fusion on Earth, we have to resolve a number of scientific and technological problems. This monograph includes selected chapters on nuclear physics and mechanical engineering within the scope of nuclear fusion.